By His Excellency Samuel Huntington Esquire. Governor and commander in chief of the state of Connecticut. A proclamation : ... Friday, the third day of April next, to be observed as a day of humiliation, fasting and prayer ... Given at Norwich, the 10th day of March ... 1795 ([Printed by T. & S. Green?], 1795)
March 10, 1795 broadside issued by Governor Samuel Huntington of Connecticut, proclaiming April 3rd as a day of fasting and prayer to seek God's favor in all the public affairs of the country.